CHILD PROTECTION IN THE PERSPECTIVE OF MULTICULTURALISM: BRIDGING TRADITIONAL VALUES AND MODERN LEGAL POLICY - Sunarto, Muhammad Zainuddin (JURNAL HAKAM, 2025)
This study aims to analyze how child protection principles can be reconciled with traditional values through a multiculturalism approach. In Indonesia, which is rich in ethnic, cultural, and religious diversity, child protection often faces significant challenges due to the differences between positive law and local cultural practices. Some traditional values, such as child marriage and corporal punishment as a form of discipline, often conflict with the child rights principles outlined in national and international law. This approach suggests the need for reconciliation between existing social norms in society and proactive legal policies that protect children. Through inter-cultural dialogue, reinterpretation of child-friendly religious values, and education based on universal human rights, child protection policies can become more contextual and effective. This study reveals that to create an ideal child protection system, cooperation between positive law and traditional values is required. The research is expected to contribute to the development of inclusive, just, and sustainable child protection policies that ensure children's rights in a safe, fair, and dignified environment.